Tunisian School Libraries: Structuring and Organizing Options Towards Modernity (The International Journal for Scientific Research, 2024)
School Libraries and information centers are part of a complex educational environment supervised by the Ministry of National Education and its regional and local representations. These libraries are also subject to the intervention of multiple actors in terms of collection, documentary funds, processing and exercise of administrative authority over them.School libraries require a legal framework that regulates them, regulates their tasks and roles, and determines their relationships with other associated structures ... These libraries need librarians equipped with professional competence and ambition to enable them to implement strategies and programs related to reading and to exploit information resources. The recruitment, appointment, promotion and transfer of these librarians must also be supervised by a known and controlled administrative structure made up of stakeholders in the field of libraries and documentation on the one hand and the various people dealing with school's libraries on the second hand. This paper attempts to answer: is the current legal and regulatory framework sufficient for school libraries to achieve what they aspire to be in our current era?Answering to this question requires identifying, developing and studying the current legal framework governing school libraries and the guides to the procedures adopted for their management, in addition to the list of libraries subject to the supervision of the Tunisian Ministry of Education. Also, how to equip them, award their accreditations ...The second part of the article is devoted to the presentation of some possible structural, organizational and procedural solutions for the administrative and technical supervision of the area of libraries and documentation and the formulation of a program or of a plan to help the school libraries keeping pace with technology and be an effective support for the progress of the education system and the improvement of the academic and cognitive results of its visitors, which gives them a central place in school life. To formulate these solutions, we rely mainly on theoretical and professional references, comparing the field of libraries and documentation with similar or close fields, and on the experiences of countries where school libraries occupy an important place and play a role essential in the school life of students and teachers.To achieve the objectives, we relied on the descriptive and analytical approach because it is characterized by realism which is in line with this study which deals with the analysis of the structure and management of school libraries in Tunisia.
Keywords: School Libraries; Restructuring; Legal Framework; Organization; Tunisia